Genetic prediction of blood metabolites mediating the relationship between gut microbiota and Alzheimer’s disease: a Mendelian randomization study - Chen, Guanglei; Jin, Yaxian; Chu, Cancan; Zheng, Yuhao; Chen, Yunzhi; Zhu, Xing (Frontiers in Microbiology, 2024)
Background: Observational studies have suggested an association between gut microbiota and Alzheimer's disease (AD); however, the causal relationship remains unclear, and the role of blood metabolites in this association remains elusive. Purpose: To elucidate the causal relationship between gut microbiota and AD and to investigate whether blood metabolites serve as potential mediators. Results: After adjustment for reverse causality and MVMR correction, class Actinobacteria (OR: 1.03, 95% CI: 1.01-1.06, P = 0.006), family Lactobacillaceae (OR: 1.03, 95% CI: 1.00-1.05, P = 0.017), genus Lachnoclostridium (OR: 1.03, 95% CI: 1.00-1.06, P = 0.019), genus Ruminiclostridium9 (OR: 0.97, 95% CI: 0.94-1.00, P = 0.027) and genus Ruminiclostridium6 (OR: 1.03, 95% CI: 1.01-1.05, P = 0.009) exhibited causal effects on AD. Moreover, 1-ribosyl-imidazoleacetate levels (-6.62%), Metabolonic lactone sulfate levels (2.90%), and Nonadecanoate (19:0) levels (-12.17%) mediated the total genetic predictive effects of class Actinobacteria on AD risk. Similarly, 2-stearoyl-GPE (18:0) levels (-9.87%), Octadecanedioylcarnitine (C18-DC) levels (4.44%), 1-(1-enyl-stearoyl)-2-oleoyl-GPE (p-18:0/18:1) levels (38.66%), and X-23639 levels (13.28%) respectively mediated the total genetic predictive effects of family Lactobacillaceae on AD risk. Furthermore, Hexadecanedioate (C16-DC) levels (5.45%) mediated the total genetic predictive effects of genus Ruminiclostridium 6 on AD risk; Indole-3-carboxylate levels (13.91%), X-13431 levels (7.08%), Alpha-ketoglutarate to succinate ratio (-13.91%), 3-phosphoglycerate to glycerate ratio (15.27%), and Succinate to proline ratio (-14.64%) respectively mediated the total genetic predictive effects of genus Ruminiclostridium 9 on AD risk. Conclusion: Our mediation MR analysis provides genetic evidence suggesting the potential mediating role of blood metabolites in the causal relationship between gut microbiota and AD. Further large-scale randomized controlled trials are warranted to validate the role of blood metabolites in the specific mechanisms by which gut microbiota influence AD.